Rational tailoring of the electronic structure for the SrxNaTayO3 semiconductor: Insights into its enhanced photoactivity and optical property. (June 2021) - Wang, Liping; Guo, Jingru; Yang, Guangpeng; Yu, Deyou; Wang, Dong; Guo, Feng; Guan, Weisheng
Abstract: NaTaO3 (NTO), as a popular photocatalyst with the prominent redox ability, largely straddles across the conduction band minimum (CBM) and valence band maximum (VBM) edge over Fermi level. Pristine NTO exhibits the poor light-harvesting ability and the rapid recombination of electron-hole pairs. We proposed an effective method to improve the photocatalytic property of NTO (ABO3 -type) by substituting B site with Sr. The Srx NaTay O3 (SNTO) exhibited the boosted photocatalytic activity toward tetracycline oxidation under solar light irradiation. The rate constant for S0.5 NTO (molar ratio of Sr: Ta = 1 : 2) was 5.1 times higher than the pure NTO. DFT results indicated that the Sr 3d orbital combining the O 2p and Ta 5d hybrid orbitals, widened the VB of SNTO. The band gap was narrowed from 3.86 to 2.82 eV after Sr substitution, which enhanced its light-harvesting ability. The VBM moved upward for 1.42 V and the CBM moved upward for 0.38 V. The shifts of the CBM and VBM, together with the more stretched Ta–O–Ta configuration, highly facilitated the electron-hole pair separation in SNTO. These electronic structure changes accounted for the significant photocatalytic performance enhancement of NaTaO3 via Sr substitution for B-site-Ta. Graphical abstract: Image 1 Highlights: S0.5 NTO semiconductor exhibited enhanced photoactivity for TC removal. The substitution of Ta atom by Sr atom altered the electronic structure of NaTaO3 . The more stretched Ta–O–Ta configuration in SNTO facilitated the charge separation. Sr 3d orbital widened the valence band of SNTO.